Associations of pre-pregnancy impaired fasting glucose and body mass index among pregnant women without pre-existing diabetes with offspring being large for gestational age and preterm birth: a cohort study in China - Wei Bao; Ruoling Chen; Qingguo Zhao; Xinhong Zhu; Yizhen Yu; Jie Tang; Henning Tiemeier; Amanda Rodney; Mingzhen Li; Dongming Huang (BMJ Open Diabetes Research & Care)
Introduction Associations of pre-pregnancy impaired fasting glucose (IFG) and body mass index (BMI) with large for gestational age (LGA) and preterm birth (PTB) have been poorly understood. We aimed to investigate the associations of maternal BMI, separately and together with pre-pregnancy IFG, with LGA and PTB in Chinese population. We also aimed to quantify these associations by maternal age.Research design and methods This was a retrospective cohort study of women from the National Free Preconception Health Examination Project with singleton birth from 121 counties/districts in 21 cities of Guangdong Province, China, from January 1, 2013 to December 31, 2017. Women were included if they did not have pre-existing chronic diseases (diabetes, hypertension, etc). Participants were divided into eight groups according to their BMI (underweight (BMI <18.5 kg/m2), normal weight (18.5–23.9 kg/m2), overweight (24.0–27.9 kg/m2), and obesity (≥28.0 kg/m2)) and pre-pregnancy fasting glucose status (normoglycemia (fasting glucose concentration <6.1 mmol/L) and IFG (6.1–7.0 mmol/L)). Adjusted incidence risk ratios (aIRRs) and 95% CIs of LGA, severe LGA, PTB and early PTB were estimated.Results We included 634 030 women. The incidences of LGA, severe LGA, PTB and early PTB for the study population were 7.1%, 2.5%, 5.1% and 1.1%, respectively. Compared with normal weight mothers with normoglycemia, overweight and obese mothers irrespective of IFG had a higher risk of LGA (eg, obesity with IFG aIRR 1.85 (1.60–2.14)) and severe LGA (eg, obesity with IFG 2.19 (1.73–2.79)). The associations of BMI and pre-pregnancy fasting glucose status with LGA were similar found among women of all age groups. Underweight with normoglycemia had 6.0% higher risk of PTB (1.06 (1.03–1.09)) and 8.0% higher risk of early PTB (1.08 (1.02–1.17)), underweight with IFG had 14.0% higher risk of PTB (1.14 (1.02–1.27)), and obese mothers with IFG had 45.0% higher risk of PTB (1.45 (1.18–1.78)). The associations of BMI and pre-pregnancy fasting glucose status with PTB differed by maternal age.Conclusion Overweight and obesity regardless of IFG were associated with an increased risk of LGA, and these associations were similarly observed among mothers of all age groups. Underweight regardless of IFG, and obesity with IFG were associated with an increased risk of PTB, but the associations differed by maternal age. Findings from this study may have implications for risk assessment and counselling before pregnancy.